Variants of weighted sticker systems with different weighting spaces - Fong, Wan Heng; Gan, Yee Siang; Sarmin, Nor Haniza; Turaev, Sherzod (Science and Knowledge Research Society, 2017)
Sticker systems have been introduced as one of the DNA computing models by using the recombination behavior of DNA molecules in 1998. Abstractly, the systems use the Watson-Crick complementary principle of DNA molecules to perform the computation in generating new strings. By associating some weights to the axioms and dominoes of sticker system, a new version of restricted sticker system namely weighted sticker system has been introduced. In this paper, we study the generative power of weighted sticker systems by considering the languages generated by weighted sticker system with different weighting spaces and cut-points. The relations of the languages generated by weighted sticker systems in the Chomsky hierarchy are also investigated.